Dimensionality, Function and Performance of Carbon Materials in Energy Storage Devices. Issue 4 (28th May 2021) - Xiao, Jing; Han, Junwei; Zhang, Chen; Ling, Guowei; Kang, Feiyu; Yang, Quan‐Hong
Abstract: Carbon materials show their importance in electrochemical energy storage (EES) devices as key components of electrodes, such as active materials, conductive additives and buffering frameworks. To meet the requirements of vastly developing markets related to EES, especially for electric vehicles and large scale energy storage, the rational design of functional carbon materials with the basis of a deep understanding of the structure‐property relationships is demanded, in which dimensionality variations and hybridizations of the carbon materials play critical roles in improving electrochemical performances of EES devices. This review focuses on the dimensionality manipulation in functional carbon materials, including transition, matching and integration, to optimize the reaction space, interface and framework in electrodes, respectively. This review gives a comprehensive review on how the dimensionality manipulation improves performance of the carbon‐based electrodes in kinetics optimization, electron transfer acceleration, mechanical stabilization and thermal dissipation upon charging/discharging. The report ends with a critical perspective on the future challenges facing carbon‐based electrodes with dimensionality dependence. The progress highlighted here is expected to provide a guidance for the precise design and targeted synthesis of dimensionality varied carbon‐based electrode materials towards safe and high performance EES devices and the resulting optimized energy deployments. Abstract : The dimensionality design of functional carbon materials towards high‐energy and high‐power electrochemical energy storage (EES) devices is summarized as dimensionality transition, matching and integration. Rational dimensionality manipulations show great potential to effectively tune the carbon functions to enhance the ion/electron conduction, stress and thermal‐transfer efficiencies, finally building up high performance EES devices.